2022
DOI: 10.3389/fped.2022.913586
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation: Association With Serum Cytokines in Pediatric Hematopoietic Stem Cell Transplantation

Abstract: Vitamin D deficiency is prevalent in pediatric patients presenting for hematopoietic stem cell transplantation (HSCT) and has been linked to poor clinical outcomes. Using the data from a randomized control trial, in this paper we explore the effects of vitamin D supplementation on circulating cytokine levels during pediatric HSCT (www.clinicaltrials.gov as NCT03176849). A total of 41 children, 20 received Stoss therapy and 21 children received standard of care vitamin D supplementation. Levels of 25(OH)D and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Cytokine levels that were significantly lower in high dose groups were IP10, monokine induced by gamma, and regulated upon activation, normal T cell expressed and secreted. 57 Bodea et al 58 assessed Stoss dose treatment in pediatric HSCT patients by randomized control and concluded that at day +30, 25-OHD levels were significantly higher (P = 0.04) in the Stoss cohort compared to the control. Their follow-up study (2022) compared vitamin D status and its impact on early (day +30) post-HSCT outcomes, specifically acute GVHD, immune recovery, infection rates, and survival.…”
Section: Variables That Impact Vitamin and Mineral Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine levels that were significantly lower in high dose groups were IP10, monokine induced by gamma, and regulated upon activation, normal T cell expressed and secreted. 57 Bodea et al 58 assessed Stoss dose treatment in pediatric HSCT patients by randomized control and concluded that at day +30, 25-OHD levels were significantly higher (P = 0.04) in the Stoss cohort compared to the control. Their follow-up study (2022) compared vitamin D status and its impact on early (day +30) post-HSCT outcomes, specifically acute GVHD, immune recovery, infection rates, and survival.…”
Section: Variables That Impact Vitamin and Mineral Requirementsmentioning
confidence: 99%
“…Findings from this study also suggest that high doses (Stoss dose) of vitamin D diminished proinflammatory cytokine responses post‐HSCT. Cytokine levels that were significantly lower in high dose groups were IP10, monokine induced by gamma, and regulated upon activation, normal T cell expressed and secreted 57 . Bodea et al 58 assessed Stoss dose treatment in pediatric HSCT patients by randomized control and concluded that at day +30, 25‐OHD levels were significantly higher ( P = 0.04) in the Stoss cohort compared to the control.…”
Section: Mnt: Screening Nutrition Assessment and Determination Of Mnt...mentioning
confidence: 99%
“… 7 Perhaps even more worrisome is that the vitamin D deficiency uncovered in this vulnerable population was persistent and associated with decreased overall survival. 7 , 8 , 9 , 10 , 11 Compared with deficient vitamin D levels, normal vitamin D levels before transplant and in the early posttransplant period have been associated with a lower incidence of graft-versus-host disease (GVHD), lower levels of proinflammatory cytokines, and improved immune reconstitution. 11 , 12 , 13 With aggressive enteral supplementation, we have been able to significantly improve outcomes and quality of life for many of these children.…”
Section: Introductionmentioning
confidence: 99%